Suitability of Bacteria in Bioremediation Techniques Common for Petroleum-Related Pollutions - Fenibo, Emmanuel Oliver (The Asia Journal of Applied Microbiology, 2021)
Petroleum hydrocarbon is an energy source that drives our modern society and at the same time impacts the environment. The consequences of hydrocarbon pollution range from microbial diversity distortion to cancer scourge in humans. To reverse these negative trends imposed by the contaminated environment, deliberate remediation steps, need to be employed, which depend on physical, chemical, and biological mechanistic principles. The physicochemical approach is quick-oriented but is more expensive relative to the biological option. The latter uses microorganisms, their parts, or enzymes to decontaminate and detoxify hazardous fractions of hydrocarbons into benign products. This biotechnology is referred to as bioremediation. Bioremediation effectiveness is achieved through the implementation of various techniques that are carried out under aerobic or anaerobic conditions or in ex-situ or in-situ. However, the aeration-related condition is the most deciding factor for microbial adaptation and survival. In aerobic conditions, fungi, bacteria, and algae contribute actively in the biotransformation and detoxification process, thus give the best result in such circumstances. However, in an anoxic environment, the prominence of bacteria comes into play (due to their ability to thrive in extreme environments) in degrading the contaminants into less harmful compounds. Thus, bacteria stand the chance of been used as the most resourceful biological tool for petroleum biotechnology including environmental remediation of extreme environments due to their high adaptive index value. Moreover, the hydrocarbon impacted environment is often characterized by high salinity, extreme temperatures, high pressure, and extreme pH.